Total costs and budgetary effects of adaptation to climate change: an assessment for the European Union - Osberghaus, Daniel; Reif, Christiane (Mannheim, 2010)
"In the aftermath of the climate conference in Copenhagen in December 2009 (15th Conference of the Parties of the United Nations), two issues appear to have played a determinant role in the negotiation discourse in protecting the global climate. First, different views on fairness considerations in sharing the burden of the greenhouse gas mitigation costs: Developed countries are historically the main contributors to climate change, while in some newly industrializing economies, notably China, emissions grow at an unprecedented rate. What is a fair way to share the responsibilities among developing and developed countries in the containment of global emissions? In international climate policy, different notions of equity have been proposed supported by different countries. The lack of consensus on equity principles has informed much of the exchanges between the United States and China. These two largest emitters worldwide have managed to stay clear of binding commitments to date. Second, coordination difficulties are displayed by the many participants to the climate negotiations: The Copenhagen Accord has introduced a nonbinding "pledge and review" mechanism where individual countries define voluntary emission reduction targets to reduce greenhouse gas emissions before 2020. Can this emergent institution prove successful as a first stage to achieve the required global coordination? Against this background, this paper is concerned with the drivers of cooperation among groups of unrelated individuals faced with a coordination game requiring multilateral effort in order to reach a target and avoid losses to all members. Free riding and coordination difficulties are held to be the primary causes of cooperation breakdown among nonrelatives. These thwarting effects are particularly severe in the absence of effective monitoring institutions capable of sanctioning deviant behavior. A growing literature however stresses the importance of non-economic factors in explaining human behavior; therefore, instruments that go beyond the traditional incentives might prove effective in facilitating the task. Given the empirical nature of the problem, we address it by means of a controlled laboratory experiment. To this end, we extend an experiment regarding a framed threshold public goods game with distinctive elements such as inequality and commitment as salient features of the ongoing debate over how best to share the "common but differentiated responsibilities" of climate change. We have built upon the game proposed by Milinski et al. (2008) to explore these further aspects that were not captured by the original design, and that we deem important both at the theoretical and policy level. The experimental results show that the real-world features introduced in the game have deep consequences on the cooperation level. Both claims that the inequality disrupts and the commitments help coordination are supported by the data. Thereby the experiment clearly shows the conditions under which subjects effectively coordinate their efforts to avoid the climate catastrophe: All successful groups agreed on a common equity notion and eliminated inequality while failing groups often disagreed about the reduction of inequality. In that context, the announcement of unbinding targets is particularly helpful to solve the coordination problem."